Lipooligosaccharide Structure is an Important Determinant in the Resistance of Neisseria Gonorrhoeae to Antimicrobial Agents of Innate Host Defense - Balthazar, Jacqueline T.; Gusa, Asiya; Martin, Larry E.; Choudhury, Biswa; Carlson, Russell; Shafer, William M. (Frontiers in Microbiology, 2011)
The strict human pathogen Neisseria gonorrhoeae has caused the sexually transmitted infection termed gonorrhea for thousands of years. Over the millennia, the gonococcus has likely evolved mechanisms to evade host defense systems that operate on the genital mucosal surfaces in both males and females. Past research has shown that the presence or modification of certain cell envelope structures can significantly impact levels of gonococcal susceptibility to host-derived antimicrobial compounds that bathe genital mucosal surfaces and participate in innate host defense against invading pathogens. In order to facilitate the identification of gonococcal genes that are important in determining levels of bacterial susceptibility to mediators of innate host defense, we used the Himar I mariner in vitro mutagenesis system to construct a transposon insertion library in strain F62. As proof of principle that this strategy would be suitable for this purpose, we screened the library for mutants expressing decreased susceptibility to the bacteriolytic action of normal human serum (NHS). We found that a transposon insertion in the lgtD gene, which encodes an N-acetylgalactosamine transferase involved in the extension of the α-chain of lipooligosaccharide (LOS), could confer decreased susceptibility of strain F62 to complement-mediated killing by NHS. By complementation and chemical analyses, we demonstrated both linkage of the transposon insertion to the NHS-resistance phenotype and chemical changes in LOS structure that resulted from loss of LgtD production. Further truncation of the LOS α-chain or loss of phosphoethanolamine (PEA) from the lipid A region of LOS also impacted levels of NHS-resistance. PEA decoration of lipid A also increased gonococcal resistance to the model cationic antimicrobial polymyxin B. Taken together, we conclude that the Himar I mariner in vitro mutagenesis procedure can facilitate studies on structures involved in gonococcal pathogenesis.